The pattern and prevalence of lymphatic spread in thoracic oesophageal squamous cell carcinoma - Chen, Junqiang; Liu, Suoyan; Pan, Jianji; Zheng, Xiongwei; Zhu, Kunshou; Zhu, Ji; Xiao, Jinrong; Ying, Mingang (European journal of cardio-thoracic surgery, 2009)
Background: Oesophageal squamous cell carcinoma (SCC) is a common type of cancer in China. The knowledge of its pattern of lymphatic metastasis would be of clinical value for surgical and radiation oncologists to treat this disease. Material and methods: A large series of 1850 thoracic oesophageal SCC was retrospectively analysed after extended oesophagectomy with three-field lymphadenectomy (3FL). Specimens were assessed for pattern of lymphatic spread. Result: Of the 1850 patients, 1081 (58.4%) developed mediastinal, cervical and/or abdominal node metastases. The lymphatic metastasis rates were 35.6%, 22.2%, 26.5%, 6.1% and 26.5%, respectively, for the cervical, upper, middle, lower mediastinal nodes and abdominal nodes. The adjacent mediastinal node metastasis alone occurred in 5.5% of patients, and the multiple level or skip node spread accounted for 20.9% and 73.6% of patients with node metastases. Upward lymphatic spread developed in 46.4% of patients, both up- and downward in 33.2%, and the downward, 20.5%. For the upper oesophageal SCC, the most common node metastasis was in the cervical (49.5%) and followed by the upper mediastinal (28.7%), middle mediastinal (11.4%), abdominal (8.0%) and lower mediastinal (1.4%) nodes. For the middle oesophageal SCC, the highest incidence of node spread was also in the cervical (35.0%) and similar rates in the middle mediastinal (29.8%), abdominal (27.2%) and upper mediastinal (22.4%) nodes, but the least in the lower mediastinal (6.0%) node. For the lower oesophageal SCC, more node metastasis occurred in the abdominal (51.7%), and followed by the middle mediastinal (25.6%), cervical (17.2%), lower mediastinal (13.9%) and upper mediastinal (10.0%). However, the lymphatic metastasis rates of the upper, middle and lower thoracic oesophageal SCC were similar. The unfavourable factors for lymphatic metastasis were long oesophageal lesion (p ≪ 0.000), late T stage (p ≪ 0.000) and poor differentiation of tumour cells (p ≪ 0.000). Conclusion: The prevalence was: (1) lymphatic spread prone to the upward in the upper oesophageal SCC, downward in the lower one and both up- and downward in the middle one with in favour of the upward and (2) multiple level and skip node metastases were very often seen. The unfavourable factors for node spread were long oesophageal lesion, late T stage and poor differentiation of tumour cells.